If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 151 + -3x = 6x + 16 Reorder the terms: 151 + -3x = 16 + 6x Solving 151 + -3x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 151 + -3x + -6x = 16 + 6x + -6x Combine like terms: -3x + -6x = -9x 151 + -9x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 151 + -9x = 16 + 0 151 + -9x = 16 Add '-151' to each side of the equation. 151 + -151 + -9x = 16 + -151 Combine like terms: 151 + -151 = 0 0 + -9x = 16 + -151 -9x = 16 + -151 Combine like terms: 16 + -151 = -135 -9x = -135 Divide each side by '-9'. x = 15 Simplifying x = 15
| 100000=10 | | 0.001=10-3 | | 95-2x=9x+18 | | 7x+35=-5(3x+8) | | 2-5x=10-7x | | 7(6X+1)=42X+7 | | 4(x-8)=2(x-3) | | 9+3x=25+x | | 3x-3=12x-102 | | 15+4x=7x-3 | | 5x-8=52 | | q=2n+2v | | 4p+3q=39 | | 9x-15=0 | | 8x-9w+4y+5w+5x+7y= | | p=3m+3w | | 74-3x=10x+22 | | -3X=-21 | | 7Y-9=8Y-2 | | 6+3x=28+x | | 4x-5=11x-54 | | 4x-5=11-54 | | 3x+39=9x+2 | | -3=X+1 | | 6x+64=12x+14 | | 6(Y+9)+Y=(Y+5)+6 | | -4Y+8=-4(2Y+4) | | -Z-9Z=5Z-5-4Z | | 12x-1=72 | | 6x=-50 | | -3x=9 | | 12x=-60 |